The Influence of Wages, Work Motivation, and the Environment Work on the Performance of Private Employees in Banjarmasin - Kastalani Fazrin (Journal of Organizational Performance and Analysis, 2026)
This study aims to analyze the influence of wages, work motivation, and work environment on the performance of private-sector employees in Banjarmasin. Employee performance is a crucial factor in determining organizational success, as it reflects the effectiveness and productivity of human resources in achieving organizational objectives. Wages, work motivation, and work environment are considered important determinants that can influence employees’ willingness and ability to perform their duties effectively. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to private employees working in various companies in Banjarmasin.. The findings indicate that wages have a positive and significant effect on employee performance, suggesting that fair and adequate compensation encourages employees to work more productively. Work motivation also has a positive and significant influence on employee performance, indicating that motivated employees tend to demonstrate higher levels of commitment and achievement. Furthermore, the work environment significantly affects employee performance, showing that a comfortable, safe, and supportive workplace enhances employees’ effectiveness and efficiency. Simultaneously, wages, work motivation, and work environment have a significant positive effect on employee performance. These findings are consistent with previous studies that emphasize the importance of compensation, motivation, and workplace conditions in improving employee performance.